Teachers' strategies in Teaching Writing During Covid-19 Pandemic at IAIN Madura - Hobbatul Qomariyah (Language-Edu, 2021)
In the Indonesian educational context, there was an obvious changes in the implementation of the teaching in learning process. In former context, teaching activities mostly took place in classroom synchronously between teacher and students. But now, during the time of COVID-19 pandemic, it changes to online learning. “In the education sector, this phenomenon certainly has as strong impact on how the learning process should be conducted. The quick solution is by utilizing online learning as what has been suggested by the Indonesian education authority” as stated (Widiastuti, Mantra, & Sukoco, 2020). This study explain the teachers’ strategies in teaching writing during 19 pandemic at IAIN Madura. There are many strategies that used by the teachers’ writing that: planning, drafting and editing.